Analisis Strategi Bisnis Pegadaian Purwokerto dengan Metode Matriks SPACE untuk Menentukan Posisi Strategis Perusahaan - Adzra Arfika Yovi Maghfira; Anggun Kurnia Sustikarini; Devi Saftri Yuliani; Yoiz Shofwa Shafrani (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
SPACE Matrix (Strategic Position and Action Evaluation) is a management strategy that assesses the company's competitive position based on four main dimensions, namely two internal factors (Financial Strength and Competitive Advantage) and two external factors (Industry Strength and Environmental Stability This study analyzes the strategic position of Pegadaian Purwokerto with the SPACE Matrix through a qualitative descriptive approach. To provide a complete picture, data were collected from primary and secondary sources. The evaluation results show that Pegadaian has fairly stable financial and industrial strength, as well as relatively stable competitiveness and environmental conditions. Determining the coordinates in the SPACE Matrix places Pegadaian Purwokerto in the aggressive quadrant, which indicates that the company has opportunities and internal strengths to actively develop its business. The recommended strategies include market penetration and market development, with the use of the SWOT matrix as a tool to formulate a comprehensive and effective strategy. These findings provide strategic guidance for Pegadaian Purwokerto in utilizing strengths and opportunities for sustainable growth.